An Analysis of English Grammar in the Perspective of Nahwu - Muh Shofiyudin; Hamidaturrohmah Hamidaturrohmah; Fikky Nuryah Tholhah; Lukluan Mansuro (JALL (Journal of Applied Linguistics and Literacy), 2023)
The mastery of English as an international language can be the main key to face some substantial challenges in this era. However, the difficulty in mastering English is such a big problem for learners, some learners still often encounter errors in learning English. One of the factors caused errors in English is a contrast from one language to another in which there are various differences and similarities, especially in the language structures or syntax. Based on the problem, for further studying English grammar needs to analyze its inherent characteristics. This study aims to identify and analyze the similarities and differences between English grammar and Nahwu, as the language structure of Arabic. This study is a qualitative descriptive research. The data was gathered through library research. The instruments used are books, journals, encyclopedias, periodicals, papers, and articles providing data related to the topics of this study. Analysis contrastive was used to evaluate for correctness, applicability, and dependability of the acquired data, which was then described and analyzed to form of conclusions. The finding showed that there are several similarities and differences between 1) part of speech, word classification in English and in Arabic called as kalimah (كلمة). 2) English Tenses and the use of fi’il in Arabic syntax or nahwu. There are eight categories of part of speech in English and three categories of kalimah  (كلمة) in Arabic. Part of speech consists of: noun, pronoun, verb, adverb, adjective, preposition, conjunction dan interjection. Then kalimah  (كلمة) in Arabic has isim (إسم), fi’il (فعل) and huruf (حرف). Amount of every categories are different due to the different categories used.